2010
DOI: 10.1111/j.1538-7836.2010.03771.x
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of diagnostic tests for clinically suspected upper extremity deep vein thrombosis: a systematic review

Abstract: To cite this article: Di Nisio M, van Sluis GL, Bossuyt PMM, Bü ller HR, Porreca E, Rutjes AWS. Accuracy of diagnostic tests for clinically suspected upper extremity deep vein thrombosis: a systematic review. J Thromb Haemost 2010; 8: 684-92.Summary. Background: The best available test for the diagnosis of upper extremity deep venous thrombosis (UEDVT) is contrast venography. The aim of this systematic review was to assess whether the diagnostic accuracy of other tests for clinically suspected UEDVT is high en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
106
0
7

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 157 publications
(117 citation statements)
references
References 34 publications
(63 reference statements)
0
106
0
7
Order By: Relevance
“…The algorithm is therefore of unknown value in that population. Ultrasonography is a sensitive (84%-97%) and specific (87%-96%) diagnostic modality that is noninvasive and readily available 22 . In cases in which ultrasonography is inconclusive, other modalities should be considered.…”
Section: Current Oncology-volume 22 Number 1 February 2015mentioning
confidence: 99%
“…The algorithm is therefore of unknown value in that population. Ultrasonography is a sensitive (84%-97%) and specific (87%-96%) diagnostic modality that is noninvasive and readily available 22 . In cases in which ultrasonography is inconclusive, other modalities should be considered.…”
Section: Current Oncology-volume 22 Number 1 February 2015mentioning
confidence: 99%
“…Table 11 summarizes the quality of evidence and frequency of potential clinical outcomes for the various diagnostic strategies. [217][218][219][220][221][222][223][224][225][226][227][228] …”
Section: Mrimentioning
confidence: 99%
“…Recent studies have demonstrated the usefulness of duplex ultrasonography in detecting and locating preoperative or postoperative thrombosis. 8,10,22,23) To date, most studies have been conducted using Western populations with respect to the incidence rate of VTE following shoulder surgery. There is no report on an Asian population.…”
Section: Introductionmentioning
confidence: 99%
“…The prompt recognition of DVT is important because patients may develop fatal PE. 22) Duplex ultrasonography is a useful tool to screen and diagnose extremity DVT. Recent studies have demonstrated the usefulness of duplex ultrasonography in detecting and locating preoperative or postoperative thrombosis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation